2012
DOI: 10.1002/mnfr.201200067
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol ameliorates diabetes‐related metabolic changes via activation of AMP‐activated protein kinase and its downstream targets in db/db mice

Abstract: RV potentiates improving glycemic control, glucose uptake, and dyslipidemia, as well as protecting against pancreatic β-cell failure in a spontaneous type 2 diabetes model. Dietary RV has potential as an antidiabetic agent via activation of AMPK and its downstream targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
96
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(100 citation statements)
references
References 51 publications
1
96
1
2
Order By: Relevance
“…Recent studies have demonstrated that resveratrol (trans-3,5,49-trihydroxy stilbene), which is found in red grapes and blue berries, lowers blood sugar, improves lipid profile 14 and prevents developmental delays in embryos of diabetic rats. 15 Several clinical trials have been conducted to study the metabolic effects of resveratrol in diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that resveratrol (trans-3,5,49-trihydroxy stilbene), which is found in red grapes and blue berries, lowers blood sugar, improves lipid profile 14 and prevents developmental delays in embryos of diabetic rats. 15 Several clinical trials have been conducted to study the metabolic effects of resveratrol in diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…1) Recently, resveratrol has been proposed as a potential anti-metabolic syndrome compound because of its role in activating sirtuin and AMP-activated protein kinase (AMPK). [2][3][4][5] Indeed, several studies have shown that resveratrol protects mice against diet-induced obesity. [6][7][8] Resveratrol has also been shown to have a favorable effect on glucose metabolism in humans.…”
mentioning
confidence: 99%
“…Moreover, Gonzales & Orlando 13 found that resveratrol acts on the NF-κB of adipocytes by inhibiting IKK, which prevents the translocation of NF-κB to the nucleus and consequently, reduces the transcription of inflammatory genes 13 . Other studies found that resveratrol reduces IKK phosphorylation in rats' liver 32 and expression of NF-κB and the cytokines IL-1β and IL-6 in fibroblasts 33 . In addition to its effect on the insulin pathway, SIRT1 can deacetylate and consequently, inhibit NF-κB, thereby reducing the transcription of proinflammatory genes 34 .…”
Section: Discussionmentioning
confidence: 91%